Gaucer Disease in the Ashkenazi-Jewish Community of South Africa - Goldblatt, Jack (Division of Human Genetics, 2015)
Gaucher disease is a biochemical genetic disorder of the lipid storage group. It is characterised by an accumulation of a glycosphingolipid, glycosyl ceramide in the reticulo-endothelial system. The condition presents clinically with hepatosplenomegaly, haematologic and orthopaedic problems. Affected individuals suffer from chronic ill-health and debility, with a clinical course of acute exacerbations, remissions and relapses. The basic defect has been shown to be a genetically determined abnormality in the enzyme beta-glucosidase, (Brady et aZ, 1965; Patrick, 1965). The diagnosis can now be accurately confirmed by laboratory procedures, which also enable determination of carrier status. Of particular interest is the high prevalence of the condition in the Ashkenazi-Jews. Fried, (1958), in a survey of cases in Jerusalem, estimated the minimal carrier or heterozygote rate to be 1 in 25. Other studies of Ashkenazi-Jews have revealed carrier frequencies ranging from 1 in 25 to about 1 in 40. This stimulated the investigation which was initially undertaken under the supervision of Professor Beighton in the Department of Human Genetics, University of Cape Town Medical School in 1975 and 1976. Further data has been accumulated by the author as a medical registrar at Groote Schuur Hospital in the ensuing period until 1979.